Prediction of Distal Tibial Articular Extension in Tibial Shaft Fractures - Myatt, Darren; Mason, Lyndon W.; Stringer, Howard; Fischer, Benjamin (Foot & ankle orthopaedics, 2022)
Category: Trauma; Ankle Introduction/Purpose: Diaphyseal tibial fractures account for approximately 1.9% of all adult fractures. A recent registry review in Finland found an annual incidence of 15.6 per 100,000 person-years in males and 11.5 per 100,000 person-years in women. There are several studies which have demonstrated a high proportion of diaphyseal tibial fractures have ipsilateral occult posterior malleolus fractures, this ranges from 22-92.3%. Recent work by Hendrickx et al has highlighted distal third and spiral tibial shaft fracture patterns as independent predictors of occult posterior malleolus fracture. Methods: Objectives Our primary outcome in this study was to identify any factors that could predict articular extension in tibial shaft fractures. Study Design & Methods A retrospective review of a prospectively collected database was performed at Liverpool University Hospitals NH Foundation Trust between 1/1/2013 and 9/11/2020. The inclusion criteria were patients over the age of 16, with a diaphyseal tibial fracture and who underwent a CT of the affected lower limb. The articular fracture extension was categorised into either posterior malleolar (PM) or other fracture. Results: 764 diaphyseal tibial fractures were analysed, of these 300 had a CT and could be included. There were 127 intra- articular fractures. Of these, 83 (65.4%) cases were PM and 44 were other fractures. On univariate analysis, the PM fractures were associated with fibular spiral (p=-016) fractures and no fracture of the fibular (p=.003), lateral direction of the tibial fracture (p=.04), female gender (p=.002), AO classification 42B1 (p=.033) and an increasing angle of tibial fracture. However, on multivariate regression analysis the only significant factor was a high angle of tibia fracture. Other distal tibia fracture extensions were associated with no fracture of the fibular (p=.002), medial direction of tibia fracture (p=.004), female gender (p=.000), and AO classification 42A1 (p=.004), 42A2 (p=.029), 42B3 (p=035) and 42C2 (p=.032). On multivariate analysis. the lateral direction of tibia fracture, and AO classification 42A1 and 42A2 were significant factors. Conclusion: Distal tibia articular extension occurs in almost half of tibial shaft fractures. A number of factors were associated with the extension, however multivariate analysis did not create a suitable prediction model. Nevertheless, rotational tibia fractures with a high angle of fracture should have a low threshold of further investigation with a CT prior to surgical intervention.